LABOR COURSE AND CONDITION OF NEWBORNS IN WOMEN WITH PLACENTAL DYSFUNCTION DUE TO GESTATIONAL ENDOTHELIOPATHY (World Science, 2019)
The purpose of the study is to evaluate the effect of placental dysfunction caused by gestational endotheliopathy on the course of labor and the condition of the newborn. The first group consisted of 70 patients with placental dysfunction with gestational endotheliopathy confirmed by laboratory-instrumental findings in the first trimester of pregnancy. The control group included 30 pregnant women with physiological gestational course. PD secondary to GE leads to preterm birth, fetal distress, increases the percentage of caesarean section, contributes to the delay of fetal growth and birth weight, poor infant status and perinatal complications.